Shaping Climbers' Experiencescapes: The Influence of History on the Climbing Experience. (January 2020) - Vespestad, May Kristin; Hansen, Odd Birger
Climbing is increasingly popular in certain destinations, yet there is little knowledge of the influence of history on climbing and other adventure tourism experiences. Climbing destinations renowned within the climbing community may well be unknown to the broader tourist masses. Using qualitative interviews of climbers visiting the Lofoten Islands, Norway, this article examines how the historical context of climbing has played a part in shaping the climbers' experiences. The study discusses the influence of history, authenticity, storytelling, and image on today's experiencescape for climbers. It is revealed how the climbing community is influenced by history through the dissemination of stories and knowledge about places, routes, and iconic climbers. Moreover, authenticity is recognized in the perception of the place and the types of route; this includes existential authenticity, where the climbing image of Lofoten remains authentic. The climbing community together shapes the experiencescape through a mutual devotion to the climbing culture.